WINNING THE COVID WAR AS RESPONSIVE MALAYSIAN CITIZEN: SOCIAL CONFORMITY, SOCIAL COMPLIANCE AND SOCIAL OBEDIENCE - Chethiyar, Saralah Devi Mariamdaran; Vedamanikam, Mohanamerry; Das, Evangelyn Sanjana Fredrick; Nair, Rakshana Nair Janarthan; Nair, Daarwesh Nair Janarthan (LIFE: International Journal of Health and Life-Sciences, 2020)
Covid-19 (also known as Coronavirus) was detected initially at Wuhan, China has spread to over 200 countries across the globe. This deadly virus is a threat to mankind as it has killed more than 300,000 and infected more than 5 million people globally. Declared as a pandemic by the World Health Organisation (WHO), momentum is accelerating to speed the development of coronavirus vaccines. Research indicated that this virus is airborne; a person on close contact may get infected from the droplets produced from the infected person during sneezing or coughing. As the virus is given medical attention to cure the infection, equal attention is given to the social aspect to break the chain of COVID. Prevention measures become crucial where many countries have taken unprecedented measures to stop the spreading of the virus by implementing lockdown and social distancing. Lockdown and social distancing are out of norm social conducts, thus adapting them instantaneously and adhering to them at all times are indeed incredible. This study explores social conformity, social compliance and social obedience of responsive citizen in Malaysian context to win the war against COVID.